ANALYSIS OF COLFFORM BACTERIA IN THE WELL WATER AND ITS POSSIBLE BIOPATHOLOGIC EFFECTS - Hastari Wuryastuti; R Wasito; Siti Chalimah; Sri Andayani; Yuni Indraswati; Leksono Lestariyadi; Prapti K; Mohammad Amien (Jurnal Sain Veteriner, 2000)
Coliform is a Gram-negative, rod shape bacteria Some strains, especially Escherichia coli can cause diarrhea among animals aad humans. Contamination of water whith pathogenic E. coli has been associated with this disease in animals and humans.In the present study, coliform bacteria were determined with most probable number (MPN) method cultured on lactose broth and brillian green bile broth. Results indicated that the well water samples collected from the areas of Karangmalang, Sungai Code and Deresan had 150 coliform/100 ml, 210 coliform/100 ml and 460 coliform/l00 ml, respectively. Whereas, standard number of coliform organisms in drinking water recommended by World Health Organization (WHO) is 10 coliform/100 ml and is 1 E. coli/100 ml. Therefore, based on the present study, the coliform organisms content in the well water is for above its normal level value as recommended by WHO. Use of the water for daily consumption, especially as drinking water needs to be a great concern